FOREIGN NATIONALS’ PROPERTY OWNERSHIP OF CONDOMINIUM UNITS POST-ENACTMENT OF THE JOB CREATION LAW: A COMPARATIVE STUDY OF INDONESIA, THAILAND, AND TURKEY - Izzati, Inayatu Dzil; Winanti, Atik (Kertha Semaya : Journal Ilmu Hukum; Vol 13 No 7 (2025), 2025)
Penelitian ini bertujuan untuk menganalisis pengaturan kepemilikan properti oleh Warga Negara Asing terkait satuan rumah susun di Indonesia, Thailand, dan Turki serta menelaah syarat dan batasan kepemilikan satuan rumah susun bagi Warga Negara Asing menurut Peraturan Perundang-undangan yang berlaku di negara-negara tersebut. Penelitian ini menggunakan jenis penelitian yuridis normatif dengan pendekatan perundang-undangan (statute approach) dan pendekatan perbandingan (comparative approach). Hasil penelitian menunjukkan bahwa perubahan dalam UU Nomor 6 Tahun 2023 tentang Penetapan PP Cipta Kerja menjadi Undang-Undang, lebih kepada penyesuaian kebutuhan investasi global tanpa mengabaikan prinsip dasar nasionalitas. Hal ini dikarenakan rumah susun di Indonesia menganut asas pemisahan horizontal. Sehingga, seseorang bisa memiliki unit satuan rumah susun, tetapi tidak secara langsung memiliki tanahnya. Negara seperti Indonesia, Thailand, dan Turki menetapkan mekanisme hukum yang berbeda dalam mengakomodasi kepemilikan apartemen oleh WNA, seperti menetapkan harga yang lebih tinggi dibanding warga lokal, penggunaan mata uang asing dalam pembelian unit apartemen, pembatasan dalam wilayah ekonomi tertentu, mengadakan prinsip resiprositas dengan negara tujuan, serta beberapa ketentuan lainnya yang diatur dalam peraturan masing-masing negara, namun tetap dalam koridor pembatasan tertentu yang bertujuan untuk menjaga kepentingan nasional, stabilitas sosial, dan kedaulatan agraria. This study aims to analyze the regulations concerning property ownership by Foreign Nationals with respect to condominium units in Indonesia, Thailand, and Turkey, as well as to examine the conditions and restrictions on condominium unit ownership by Foreign Nationals in accordance with the prevailing laws and regulations in these countries. This research employs a normative juridical methodology with a statutory approach and a comparative approach. The findings indicate that the amendments to Law Number 6 of 2023 regarding the Ratification of the Job Creation Government Regulation into Law primarily reflect adjustments to global investment needs without disregarding the fundamental principle of nationality. This is due to the fact that condominiums in Indonesia adhere to the principle of horizontal separation, whereby an individual may own a condominium unit but does not directly own the land beneath it. Countries such as Indonesia, Thailand, and Turkey establish different legal mechanisms to accommodate foreign ownership of apartments, including imposing higher prices compared to local citizens, permitting the use of foreign currency in the purchase of apartment units, restricting ownership within certain economic zones, applying principles of reciprocity with the foreigner’s country of origin, as well as other provisions regulated under each country’s respective laws. Nonetheless, these regulations remain within certain limitations aimed at safeguarding national interests, social stability, and agrarian sovereignty.